Dietary polyphenols and their relationship to the modulation of non-communicable chronic diseases and epigenetic mechanisms: A mini-review - Felipe Tecchio Borsoi; Iramaia Angélica Neri-Numa; Williara Queiroz de Oliveira; Fabio Fernandes de Araújo; Glaucia Maria Pastore (Food Chemistry: Molecular Sciences, 2023)
Chronic Non-Communicable Diseases (NCDs) have been considered a global health problem, characterized as diseases of multiple factors, which are developed throughout life, and regardless of genetics as a risk factor of important relevance, the increase in mortality attributed to the disease to environmental factors and the lifestyle one leads. Although the reactive species (ROS/RNS) are necessary for several physiological processes, their overproduction is directly related to the pathogenesis and aggravation of NCDs. In contrast, dietary polyphenols have been widely associated with minimizing oxidative stress and inflammation. In addition to their antioxidant power, polyphenols have also drawn attention for being able to modulate both gene expression and modify epigenetic alterations, suggesting an essential involvement in the prevention and/or development of some pathologies. Therefore, this review briefly explained the mechanisms in the development of some NCDs, followed by a summary of some evidence related to the interaction of polyphenols in oxidative stress, as well as the modulation of epigenetic mechanisms involved in the management of NCDs.